Proteomic and Post‐Translational Modification Profiling of Exosome‐Mimetic Nanovesicles Compared to Exosomes. Issue 8 (3rd April 2019) - Nasiri Kenari, Amirmohammad; Kastaniegaard, Kenneth; Greening, David W.; Shambrook, Mitch; Stensballe, Allan; Cheng, Lesley; Hill, Andrew F.
Abstract: Issues associated with upscaling exosome production for therapeutic use may be overcome through utilizing artificial exosomes. Cell‐derived mimetic nanovesicles (M‐NVs) are a potentially promising alternative to exosomes for clinical applicability, demonstrating higher yield without incumbent production and isolation issues. Although several studies have shown that M‐NVs have similar morphology, size and therapeutic potential compared to exosomes, comprehensive characterization and to what extent M‐NVs components mimic exosomes remain elusive. M‐NVs were generated through the extrusion of cells and proteomic profiling demonstrated an enrichment of proteins associated with membrane and cytosolic components. The proteomic data herein reveal a subset of proteins that are highly abundant in M‐NVs in comparison to exosomes. M‐NVs contain proteins that largely represent the parental cell proteome, whereas the profile of exosomal proteins highlight their endosomally derived origin. This advantage of M‐NVs alleviates the necessity of endosomal sorting of endogenous therapeutic proteins or RNA into exosomes. This study also highlights differences in protein post‐translational modifications among M‐NVs, as distinct from exosomes. Overall this study provides key insights into defining the proteome composition of M‐NVs as a distinct from exosomes, and the potential advantage of M‐NVs as an alternative nanocarrier when spontaneous endosomal sorting of therapeutics are limited.